Proposal for a software maintenance model for small businesses in Benguela - Cruz Acosta, Roberto (2024)
This research focuses on the insufficient adaptability of the maintenance process within the life cycle of management software in small national companies, based on international standards framed in the area, which makes it difficult to guide the software maintenance execution process. The main objective is to provide the development of a software maintenance procedure adjusted to the specific needs and characteristics of small businesses. The methodology used is mixed, where the opinions of officials were recognized and the SPSS statistical program was used for data analysis. The expected results of the use and application of this maintenance management proposal will extend the useful life of the systems, making better use of the company's existing IT tools. This implies reusing solutions implemented based on current needs, avoiding throwing them away. In addition, a detailed procedure is offered that guides the performance of software maintenance in the national industry, seeking to strengthen the software industry in Angola by providing an efficient model adapted to the needs of small businesses. This study presents a proposed software maintenance procedure for small businesses in Benguela. A mixed methodology has been used and it is expected that the results will contribute to extending the useful life of the systems and improving their operability and quality. The proposal seeks to strengthen the software industry in Angola by providing an efficient model adapted to the needs of small businesses.